Beyond Correlation: Do Color Features Influence Attention in Rainforest? - Frey, Hans-Peter; Wirz, Kerstin T.; Willenbockel, Verena; Betz, Torsten; Schreiber, Cornell; Troscianko, Tomasz; Konig, Peter (Frontiers in Human Neuroscience, 2011)
Recent research indicates a direct relationship between low-level color features and visual attention under natural conditions. However, the design of these studies allows only correlational observations and no inference about mechanisms. Here we go a step further to examine the nature of the influence of color features on overt attention in an environment in which trichromatic color vision is advantageous. We recorded eye-movements of color-normal and deuteranope human participants freely viewing original and modified rainforest images. Eliminating red-green color information dramatically alters fixation behavior in color-normal participants. Changes in feature correlations and variability over subjects and conditions provide evidence for a causal effect of red-green color contrast. The effects of blue-yellow contrast are much smaller. However, globally rotating hue in color space in these images reveals a mechanism analyzing color contrast invariant of a specific axis in color space. Surprisingly, in deuteranope participants we found significantly elevated red-green contrast at fixation points, comparable to color-normal participants. Temporal analysis indicates that this is due to compensatory mechanisms acting on a slower time scale. Taken together, our results suggest that under natural conditions red-green color information contributes to overt attention at a low level (bottom-up). Nevertheless, the results of the image modifications and deuteranope participants indicate that evaluation of color information is done in a hue-invariant fashion.